Endoscopic endonasal transsphenoidal surgery for patients aged over 80 years with pituitary adenomas: Surgical and follow-up results - Fujimoto, Kenji (Surg Neurol Int, 2017)
BACKGROUND: With the rapid aging of the general population, the number of pituitary adenoma (PA) diagnosed in elderly patients is increasing. The aim of this study was to evaluate the efficacy of endoscopic endonasal transsphenoidal surgery (ETSS) for PA in patients aged ≥80 years. METHODS: We retrospectively reviewed the medical records of all patients aged ≥80 years who underwent ETSS for PA at our hospital from January 2001 through December 2014. Treatment results were assessed by the extent of surgical removal, symptom improvement, postoperative complications, and Karnofsky performance status (KPS). The results were also compared with the surgical result of PA patients aged <80 years. RESULTS: Twelve patients aged ≥80 years underwent ETSS for PA. Recovery of visual function was observed in 11 patients (91.7%). Postoperative cerebrospinal fluid (CSF) leakage was observed in 3 patients. New hormonal replacement therapy was required in 2 patients. These complications had not affected patient prognosis. During the follow-up periods, deterioration of KPS was observed in 2 patients due to pneumonia or cerebral infarction. In total, 150 PA patients aged <80 years were compared with the patients aged ≥80 years. The percentage of total removal was significantly higher in the younger patient group than that in the older one (54.0% vs 16.6%, respectively; P = 0.016). Visual improvement was observed in 93.2% of the younger patient group, which was almost equal to that in the older one. CONCLUSION: ETSS is a safe and effective surgical technique in PA patients aged ≥80 years.